The combined effects of ciprofloxacin and vitamin C on the multi drug resistant Gram-negative bacteria - Rafa, Zarin Tasnim; Rini, Shadhin Chowdhury (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2023.